Eosinophil-derived neurotoxin enhances airway remodeling in eosinophilic chronic rhinosinusitis and correlates with disease severity. (15th September 2018) - Tsuda, Takeshi; Maeda, Yohei; Nishide, Masayuki; Koyama, Shohei; Hayama, Yoshitomo; Nojima, Satoshi; Takamatsu, Hyota; Okuzaki, Daisuke; Kinehara, Yuhei; Kato, Yasuhiro; Nakatani, Takeshi; Obata, Sho; et al.
Abstract : The role of eosinophil-derived neurotoxin in chronic rhinosinusitis Abstract: Eosinophilic chronic rhinosinusitis (ECRS) is a subtype of chronic rhinosinusitis (CRS) that is characterized by intractable nasal polyp formation. Eosinophil-derived neurotoxin (EDN) is an eosinophil granule protein that is closely related to allergic inflammation, but the pathological implications of EDN in ECRS remain unknown. In this study, we evaluated the function of EDN in ECRS pathogenesis and assessed its potential as a disease activity marker. Serum EDN levels were significantly higher in patients with ECRS than in those with other nasal and paranasal diseases, and were positively correlated with clinical disease activity. Production of EDN from isolated human eosinophils was induced by stimulation with IL-5 in vitro . Human nasal epithelial cells were stimulated with EDN, and the resultant changes in gene expression were detected by RNA sequencing. Pathway analysis revealed that the major canonical pathway affected by EDN stimulation was 'regulation of the epithelial–mesenchymal transition pathway'; the only gene in this pathway to be up-regulated was matrix metalloproteinase 9 (MMP-9). Consistent with this, immunostaining analysis revealed intense staining of both EDN and MMP-9 in nasal polyps from patients with ECRS. In conclusion, our data demonstrate that serum EDN level is a useful marker for the evaluation of ECRS severity. Furthermore, EDN induces production of MMP-9 from the nasal epithelium, which may be involved in the pathogenesis of ECRS.